A Key for the Future of the Flavors in Food Industry: Nanoencapsulation and Microencapsulation - Berta Nogueiro Estevinho (2017)
Microencapsulation and nanoencapsulation have become a challenging approach to design new materials with biotechnological applications. They are used in several fields, particularly in the food industry, and are one of the most important forms of controlled release of substances.Flavors play important roles in consumer satisfaction and influence further consumption of foods. Flavors have a large scope of applications in the food industry. However, some of them are very sensitive to ambient or industrial process conditions. Flavor loss during the processing or storage of foods is a common occurrence. Flavors are very volatile, react with other components, and are susceptible to heat and moisture. In other cases, it is expected that the flavor will only be available at the moment of food ingestion or be retained in food for a longer period. For all these reasons, nano- and microencapsulation are important to protect and retain the flavors in the best conditions.Encapsulation can be used to increase the effectiveness of many compounds in the food industry and it allows the utilization of some that otherwise would be unfeasible. The main techniques of encapsulation will be presented and discussed, as well as the influence of the encapsulating agent in the controlled release processes is discussed.